2021
DOI: 10.3390/languages6040176
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Dimensional Variation in Adult Speech as a Function of Age

Abstract: We present a multidimensional acoustic report describing variation in speech productions on data collected from 500 francophone adult speakers (20 to 93 y.o.a.) as a function of age. In this cross-sectional study, chronological age is considered as a continuous variable while oral productions, in reading and speech-like tasks, are characterized via 22 descriptors related to voice quality, pitch, vowel articulation and vocalic system organization, time-related measures and temporal organization, as well as maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
2
12
0
4
Order By: Relevance
“…One frequently-discussed aspect of aging that we omit here is slowed speech or articulation rate. Readers are referred to the comprehensive studies of Schötz (2006) and Fougeron et al (2021) for results on duration and other measures not included here.…”
Section: Aging Effects On Speech Anatomy Physiology and Acousticsmentioning
confidence: 99%
See 4 more Smart Citations
“…One frequently-discussed aspect of aging that we omit here is slowed speech or articulation rate. Readers are referred to the comprehensive studies of Schötz (2006) and Fougeron et al (2021) for results on duration and other measures not included here.…”
Section: Aging Effects On Speech Anatomy Physiology and Acousticsmentioning
confidence: 99%
“…Some aspects of chronological change, especially across speakers, could reflect sound change (e.g., Reubold et al 2010) and/or stylistic factors that may change with age and interact with gender. As one possible example, Fougeron et al (2021) observed that measures of F1 and F2 ranges differed in older males and females: Males showed no significant changes in F1 range with age, whereas females did; conversely, F2 ranges changed with age in males but not females.…”
Section: Upper Vocal Tractmentioning
confidence: 99%
See 3 more Smart Citations